2009
DOI: 10.1111/j.1743-6109.2008.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Penile Deep Dorsal Venous Leakage of Erectile Dysfunction by Embedding the Deep Dorsal Vein of the Penis: A Single Center Experience with 17 Patients

Abstract: Introduction The common surgery for venous leakage was not very successful; unsatisfactory long-term results have reduced the indications for venous surgery for erectile dysfunction (ED). Aims To assess the outcomes of embedding the deep dorsal vein of the penis (EDDVP), a new surgical technique used in patients with penile deep dorsal venous leakage of ED. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(47 reference statements)
0
3
0
2
Order By: Relevance
“…In the tissue biopsy of albuginea under microscope, collagen fiber atrophy was observed. [17] Zhang et al [18] reported that the surgery of embedding deep dorsal vein of penis had achieved good effects for treatment of vein leakage ED, and 14 out of 17 patients obtained satisfying effects. Popken G reported that 122 patients who had received ligation of deep dorsal vein of penis with a total effective rate of 33%.…”
Section: Discussionmentioning
confidence: 99%
“…In the tissue biopsy of albuginea under microscope, collagen fiber atrophy was observed. [17] Zhang et al [18] reported that the surgery of embedding deep dorsal vein of penis had achieved good effects for treatment of vein leakage ED, and 14 out of 17 patients obtained satisfying effects. Popken G reported that 122 patients who had received ligation of deep dorsal vein of penis with a total effective rate of 33%.…”
Section: Discussionmentioning
confidence: 99%
“…In a further study from Chen a highly significant change in IIEF score after long-term observation was stated for patients who underwent deep dorsal vein stripping [33]. Very recently Zang reported about very good long-term success rates after deep dorsal vein embedding (100%), respectively [34].…”
Section: Basche Et Al Described a Technique Of Retrograde Embolisation Carried Out Via The Femoral Vein By Coaxial Technique Using Histoamentioning
confidence: 99%
“…Поскольку ГДВ наиболее часто становится путем патологического оттока крови от кавернозных тел при веногенной эректильной дисфункции, она считается и основным объектом хирургического вмешательства. Осуществляют ее лигирование, иссечение, склерозирование [7], погружение в дупликатуру белочной оболочки [8]. Проводят также склерозирование путей оттока от нее -вен простатического сплетения, внутренних и наружных половых вен [9,10].…”
Section: Introductionunclassified
“…В связи с этим ре дукционные хирургические вмешательства на венах полового члена не относятся к рекомендованным и не входят в стандарт лечения эректильной дисфункции [13][14][15]. Высокую эффективность, превышающую 75 % в отдаленные сроки, демонстрируют лишь отдельные клиники -приверженцы венозной хирургии -у небольшого числа пациентов, причем преимущественно молодых [8,16]. Причинами неудовлетворительных результатов считают, во-первых, то, что лечение веногенной эректильной дисфункции путем прекращения кровотока по венам не является патогенетическим, а во-вторых, то, что венозная редукция при отсутствии точной топической диагностики венозной утечки с большой вероятностью не будет радикальной [17,18].…”
Section: Introductionunclassified